Understanding Japanese tourists' shopping preferences using the Decision Tree Analysis Method - Kim, Samuel Seongseop; Timothy, Dallen J.; Hwang, Jinsoo (My University, 2010)
This study was designed to assess the factors affecting Japanese tourists’ shopping preference and intention to revisit Korea. The analytical method applied in this study was Decision Tree Analysis, which is under-utilized in tourism studies. A total of 300 questionnaires were collected on the basis of on-site survey method and used for data analysis. Among interesting findings, three groups including ‘respondents who were satisfied, accompanied, and spent US$50-300 on shopping’, ‘respondents who were satisfied, accompanied, and had a shopping expenditure of US$300-1000’ and ‘respondents who were satisfied, accompanied, and had a shopping expenditure of US$1000-5000,’ showed a high level of intention to return to Korea for the purpose of shopping. In addition, two groups ‘those who were interested in shopping in Korea, preferred a shopping mall as a shopping destination, and had an educational level of below high school’ and ‘those who were interested in shopping in Korea, preferred a shopping mall as a shopping destination, and had an educational level of a college graduate or above’ showed a higher level interest in merchandise than in shopping venue attractiveness.
Keywords: Shopping; Japanese tourists; Decision Tree Analysis; CHAID